Networks and Institutionalization: A Neo-structural Approach. - Lazega, Emmanuel (Connections (02261766), 2017)
This paper is the text prepared for the keynote address of the EUSN 2017 conference in Mainz, Germany. A short presentation of concepts reflects in part the foundations of neostructural sociology (NSS) and its use of social and organisational network analyses, combined with other methodologies, to better understand the roles of structure and culture in individual and collective agency. The presentation shows how NSS accounts for institutional change by focusing on the importance of combined relational infrastructures and rhetorics. Specific characteristics of institutional entrepreneurs who punch above their weight in institutionalization processes are introduced for that purpose, particularly the importance of multistatus oligarchs, status heterogeneity, high-status inconsistencies, collegial oligarchies, conflicts of interests and rhetorics of relative/false sacrifice. Two empirical examples illustrate this approach. The first case focuses on a network study of the Commercial Court of Paris, a 450-year-old judicial institution. The second case focuses on a network study of a fieldconfiguring event (the so-called Venice Forum) lobbying for the emergence of a new European jurisdiction, the Unified Patent Court, and its attempt to create a common intellectual property regime for the continent. For sociologists, both examples involve "studying up": they are cases of public/private joint regulation of markets bringing together these ingredients of institutionalization. The conclusion suggests future lines of research that NSS opens for the study of institutionalization, in particular using the dynamics of multi-level networks. One of the main issues raised by this approach is its contribution to the study of democratic deficits in a period of intense institutional change in Europe.